Batad Ifugao dictionary with ethnographic notes - Newell, Leonard E. (Linguistic Society of the Philippines, 1993)
A fuller version of Leonard Newell's Batad Ifugao Dictionary (1968). An ethnographic dictionary that is systematic, non-prescriptive and semantically sensitive. A compilation of nearly 7500 Ifugao words with full explanatory definitions of great ethnographic value and linguistic precision. Includes 16,000 brief English-Batad Ifugao index entries.